PERUMUSAN STRATEGI PEMASARAN BERDASARKAN ANALISIS SWOT PADA CV FORTUNA MANDIRI DI KABUPATEN BERAU - Kristanto, Rudi; Purwanto, Sayugo Adi (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2017)
The purpose of this study was to determine the optimal Rinso inventory at PT. Sinar Kalimantan at Tanjung Redeb. The average inventory method was used to analyze the data in this study.Based on the analysis and forecasting calculation, the inventory for one year (2015) for Rinso powder size 900 gr was 1,170 dos and Rinso powder size 450 gr was 1.018 dos every 3 times orders of both types Rinso powder was 8.754 x 3 times order = 26.262 dos,it was not optimal whereas based on calculation EOQ Rinso powder size 900 gr is 6,104 dos and Rinso powder size 450 gr was equal to 5,03 dos in one order of both type Rinso powder is 11.107 x 3 order = 32.985 dos it was an optimal supply because accordancing with the actual inventory and residual inventory can be used as the stock for the company.From result calculation by using EOQ tool obtain the optimal inventory result and earlier hypothesis is not accepted because contrary to research result (opposite)